Effect of Glycerol Addition as an Entrainer in Extractive Distillation for Bioethanol Purification from White Glutinous Rice Fermentation - Zuinan Dakwa; Yeti Kurniasih; Hulyadi; Yusran Khery (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Bioethanol is a renewable liquid fuel that can be produced from carbohydrate-rich biomass, including white glutinous rice (Oryza sativa var. glutinosa). However, fermentation-derived bioethanol typically contains a high proportion of water; therefore, further purification is required to improve its suitability for fuel or industrial applications. This study investigated the effect of glycerol addition as a high-boiling and hygroscopic entrainer in the extractive distillation of bioethanol produced from white glutinous rice fermentation. A quantitative laboratory experiment was conducted using 200 mL bioethanol samples with varying glycerol volumes of 0, 10, 30, 40, 50, 60, and 70 mL. The ethanol concentration in the distillate was determined based on density measurements using a pycnometer and a calibration curve prepared from ethanol standard solutions. The calibration curve demonstrated a strong linear relationship between ethanol concentration and density, expressed as ρ = −0.0017C + 1.0057, with an R² value of 0.9931. The results showed that glycerol addition increased the apparent ethanol concentration of the distillate compared with the control sample. The highest ethanol concentration was obtained with the addition of 50 mL glycerol to 200 mL bioethanol sample, producing a distillate density of 0.9200 g/mL and an ethanol concentration of 50.41%. This value represents an increase of 44.94 percentage points from the initial concentration of 5.47%. However, further increases in glycerol volume reduced the separation efficiency, most likely due to increased viscosity, which may have hindered heat and mass transfer during distillation. These findings indicate that glycerol can enhance bioethanol purification through extractive distillation when applied at an optimum volume ratio. Nevertheless, further dehydration and more rigorous analytical validation are required before the final product can be classified as fuel-grade ethanol.